Bluetooth transceivers for full duplex communications in mobile robots - Choo, S. H. (Penerbit UTM Press, 2002)
This work explores the implementation of Bluetooth technology in mobile robots. The mobile robot has the capability to move around autonomously using complicated and powerful algorithm. The algorithms are stored in the master as the server. All sensor readings from the mobile robot will be transmitted to the master and processed. Then, command or instruction for further action is transmitted from the server to the mobile robot in a bi-directional full duplex communication mode. Hence, the main â€œbrainâ€? is in the server instead of the mobile robot. This paper will focus on the interfacing between Bluetooth transceiver and Handy Board MC68HC11 micro-controller of mobile robot. For common case, a receiver and transmitter are needed for each device (robot and control unit), but with Bluetooth technology, only two Bluetooth transceivers are needed to achieve full duplex connection. This project has provided a Bluetooth enabled mobile robot. The mobile robot can be controled wirelessly via Bluetooth transceiver.